Perancangan dan Implementasi Aplikasi Android Sebagai Layanan Mobile Payment Gateway Pada Sistem Online Payment Point (SOPP) PDAM Kabupaten Malang - grifito yuan maulidina (Jurnal Jaringan Telekomunikasi, 2015)
The development of online payment systems such as the online payment point system has greatly assisted the public in processing monthly transactions such as water bills. However, in its application, this system still uses large devices such as computers and inkjet printers so that the operation takes a long time and is less efficient. Therefore, in this study, a mobile application is designed to replace the role of computers in making water bill payment transactions in the online payment point system (SOPP) of PDAM Malang Regency. The application that is connected to a database server via the internet is also integrated with a compact wireless thermal printer that can be carried anywhere and does not require ink refills so that it can speed up the transaction process and be more efficient in time, paper and space. The research method used was experimental and survey methods. The experimental method is used to test the running of the application, test the application's compatibility with the device and measure the time it takes for the application to exchange data. The survey method is used to test user satisfaction with the application.